No Time to Waste : The Challenges and Opportunities of Cleaner Trade for Vietnam - World Bank (World Bank, Hanoi, 2022)
The Twenty-sixth United Nations Climate Change Conference (COP26) was held in early November 2021 in Glasgow, Scotland, at which Vietnam’s Prime Minister, Phạm Minh Chính, pledged once again that Vietnam would be part of the global climate change solution. The country aims to increase the share of clean energy in its total primary energy supply to at least 20 percent by 2030 and 30 percent by 2045 and has pledged to phase out coal-fueled power generation and made a commitment to reach net zero emissions by 2050. Trade can be a central part of the solution to climate change Vietnam is experiencing and will have to deal with in years to come. Green trade or cleaner trade, trade in environmental or environmentally friendly goods can help Vietnam achieve not only its climate commitments but also its development ambition to become a high-income economy by 2045 as set out in the 2021–2030 Social Economic Development Strategy (SEDS). This edition of Taking Stock reviews the recent developments in the Vietnamese economy and discusses the economy’s short- to medium-term prospects, highlighting domestic and external risks associated to the COVID-19 pandemic. The second part of the report elaborates on how Vietnam can harness the impacts of climate change on its trade sector, address challenges and take advantage of new opportunities